2019
DOI: 10.1101/577981
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bayesian population receptive field modeling in human somatosensory cortex

Abstract: 21Somatosensation is fundamental to our ability to sense our body and interact with the 22

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 77 publications
5
34
3
Order By: Relevance
“…This showed that there was spatial agreement between the methods, but crucially that iMP could also estimate digit overlap ( Da Rocha Amaral et al., 2020 ). Furthermore, a study by Puckett et al. (2020) applied a Bayesian variant of population receptive field mapping ( Zeidman et al., 2018 ) to estimate receptive field size and centre of mass in S1, and showed digit preference and overlap ( Puckett et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This showed that there was spatial agreement between the methods, but crucially that iMP could also estimate digit overlap ( Da Rocha Amaral et al., 2020 ). Furthermore, a study by Puckett et al. (2020) applied a Bayesian variant of population receptive field mapping ( Zeidman et al., 2018 ) to estimate receptive field size and centre of mass in S1, and showed digit preference and overlap ( Puckett et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study by Puckett et al. (2020) applied a Bayesian variant of population receptive field mapping ( Zeidman et al., 2018 ) to estimate receptive field size and centre of mass in S1, and showed digit preference and overlap ( Puckett et al., 2020 ). These recent advances in extracting digit size and location from travelling wave data will prove useful in future, as travelling wave designs are much faster at digit mapping than event related designs ( Besle et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from characterizing the properties of voxels in response to external stimulation, the pRF modeling approach has also been extended to study resting state connectivity ( Gravel et al, 2014 ). Outside the study of visual areas, pRF modeling approaches have been successfully applied to map the spatial organization of the somatosensory cortex ( Puckett et al, 2020 ) as well as the preference and selectivity (i.e., tuning) to sound frequency in auditory cortical areas ( Thomas et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This 'population receptive field' method (Dumoulin and Wandell, 2008;Wandell et al, 2007;Winawer, 2015, 2010) has rapidly become a popular method to map the functional organization of the human brain. In addition to describing the retinotopic organization of retinal activation in cortical and subcortical brain areas, the method has been used to map the cortical representation of other stimulus features such as tonotopy (Thomas et al, 2015), numerosity (Harvey et al, 2015), tactile sensations (Puckett et al, 2020), and visual timing (Harvey et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies used phase-encoding with ‘rotating wedge’ and ‘expanding or contracting ring’ stimuli to identify RF position (Engel, 2012; Engel et al, 1994; Sereno et al, 1995), while later studies increasingly used the ‘population receptive field’ (pRF) method that estimates RF-size in addition to position (Dumoulin and Wandell, 2008; Wandell et al, 2007; Wandell and Winawer, 2015, 2010). The method is popular and has been used to map a range of visual and cognitive functions (Binda et al, 2018; Ekman et al, 2020; Harvey et al, 2020, 2015; He et al, 2019; Hughes et al, 2019; Mo et al, 2017; Poltoratski et al, 2019; Poltoratski and Tong, 2020; Puckett et al, 2020; Shao et al, 2013; Shen et al, 2020; Silson et al, 2018; Stoll et al, 2020; Thomas et al, 2015; Welbourne et al, 2018; Zuiderbaan et al, 2017), dysfunctions (Ahmadi et al, 2020; Alvarez et al, 2020; Best et al, 2019; Dumoulin and Knapen, 2018; Green et al, 2019; Schwarzkopf et al, 2014), mechanisms of brain development (Dekker et al, 2019), cortical evolution (Keliris et al, 2019; Kolster et al, 2014; Zhu and Vanduffel, 2019), and information transfer across different brain areas (Haak et al, 2013).…”
Section: Introductionmentioning
confidence: 99%